Urea Reduction Ratio for CKD Stage 5 Hemodialysis Patients at Dr Pirngadi Hospital Medan - Dasopang, Eva Sartika; Hasanah, Fenny; Handayani, Salmah; Daya, Verawati L.; Thaharah, Yelda R.; Sandika, Thalita (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Stage 5 CKD is a severe form of kidney disease with a GFR value of <15 mL/min/1.73 m2. Haemodialysis is a replacement therapy that removes metabolic waste, including urea. The text discusses a study conducted at Dr. Pirngadi Hospital in Medan City to compare pre- and post-urea values and URR (urea reduction ratio) in patients with stage 5 chronic kidney disease (CKD) undergoing haemodialysis. The study used retrospective data from CKD stage 5 patients with complete medical records and pre- and post-urea laboratory results. The results of the study revealed that the haemodialysis process was effective, with a significant difference in pre- and post-urea values (p<0.05). The average pre-urea value was 114.29 mg/dL, while the average post-haemodialysis urea value was 37.85 mg/dL. The URR was found to be 67.46%. However, it was concluded that adequate haemodialysis in stage 5 CKD patients at Dr. Pirngadi Hospital had not reached 100%.